2009
DOI: 10.1021/bi801931e
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Fused NS4A Peptide−NS3 Protease Domain To Study the Importance of the Helicase Domain for Protease Inhibitor Binding to Hepatitis C Virus NS3-NS4A

Abstract: The NS3 protein of hepatitis C virus is unusual because it encodes two unrelated enzymatic activities in linked protease and helicase domains. It has also been intensively studied because inhibitors targeting its protease domain have potential to significantly improve treatment options for those infected with this virus. Many enzymological studies and inhibitor discovery programs have been carried out using the isolated protease domain in complex with a peptide derived from NS4A which stimulates activity. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
3
14
1
Order By: Relevance
“…The SAXS data unambiguously prove the domain orientation as in the crystal structure. The experimental data cannot be reconciled with the scattering patterns computed from a full-length flaviviral NS2B/3 structure with an extended domain orientation, exemplified by the Dengue virus structure 2VBC (17) for which no satisfactory fit could be obtained (discrepancy χ ¼ 7.5; Fig. 2B).…”
Section: Interactions With Protease Residues and Comparison To Hcv Nsmentioning
confidence: 85%
See 1 more Smart Citation
“…The SAXS data unambiguously prove the domain orientation as in the crystal structure. The experimental data cannot be reconciled with the scattering patterns computed from a full-length flaviviral NS2B/3 structure with an extended domain orientation, exemplified by the Dengue virus structure 2VBC (17) for which no satisfactory fit could be obtained (discrepancy χ ¼ 7.5; Fig. 2B).…”
Section: Interactions With Protease Residues and Comparison To Hcv Nsmentioning
confidence: 85%
“…Dahl et al observed a 10-fold decrease in binding affinity of BILN2061 to the full-length NS3/4A harboring an H528S mutation (16). Thibeault et al, on the other hand, report that the full-length NS3/4A triple mutant M485A, V524A, Q526A did not lead to a significant change in K I for eight inhibitors tested (17). An example where the structural information of helicase residues was explicitly considered in the design of P2-P4 macrocyclic protease inhibitors was reported by Liverton et al (18).…”
mentioning
confidence: 99%
“…The HCV genotype 1b Con1 strain NS3-NS4A protein (FL-protease), the HCV genotype 1b J strain NS3 protease domain, and the same domain with an NS4A peptide fused to its N terminus (sc-protease) were expressed and purified as described previously (16). The NS4A peptide used for crystallography (KKGSVVIVGRIILSGRK) has also been described previously (16), as well as the depsipeptide fluorogenic substrate anthranilyl-DDIVP-Abu[C(O)-O]AMY(3-NO 2 )-TW-OH, which is derived from the NS5A-NS5B cleavage site. FL-protease and sc-protease recognize and process this substrate with a similar efficiency (16).…”
Section: Methodsmentioning
confidence: 99%
“…The NS4A peptide used for crystallography (KKGSVVIVGRIILSGRK) has also been described previously (16), as well as the depsipeptide fluorogenic substrate anthranilyl-DDIVP-Abu[C(O)-O]AMY(3-NO 2 )-TW-OH, which is derived from the NS5A-NS5B cleavage site. FL-protease and sc-protease recognize and process this substrate with a similar efficiency (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation